TINJAUAN HUKUM ISLAM TERHADAP PERBEDAAN PENERIMAAN MANFAAT ATAS PENGALIHAN LAYANAN ASURANSI SOSIAL PT ASABRI KE BPJS KETENAGAKERJAAN (Analisis Putusan Mahkamah Konstitusi Nomor 6/PUU-XVIII/2020) - Mira Apriani Mira Apriani (Jurnal ini dipublikasikan oleh Pusat Penelitian dan Pengabdian Publikasi (P3M) STAI Nahdlatul Watan Samawa-licensed under a Creative Commons Attribution-ShareAlike 4.0 International License., 2023)
The existence of Article 57 letter (e) and Article 65 Paragraph (1) of Law Number 24 of 2011 concerning BPJS can harm the constitutional rights of Active and Retired Members of the TNI and Polri regarding receiving benefits from social security.The problems in this research are, 1) What are the considerations of the Constitutional Court judges in the Constitutional Court decision Number 6/PUU-XVIII/2020. 2) What is the review of Islamic law regarding the decisions of the Constitutional Court judges in the Constitutional Court decision Number 6/PUU-XVIII/2020. The purpose of this study is to analyze how the judges consider the decision of the Constitutional Court Number 6/PUU-XVIII/2020 and analyze how Islamic law reviews the decisions of the judges of the Constitutional Court in the decision of the Constitutional Court Number 6/PUU-XVIII/2020. The type of research used in this research is library research which is descriptive-normative in nature and originates from primary, secondary and tertiary legal materials, then the data is processed and analyzed in the form of qualitative analysis.Constitutional Court Decision Number 6/PUU-XVIII/2020 states that Article 57 letter e and Article 65 Paragraph (1) Law Number 24 of 2011 concerning the Social Security Administering Body (BPJS) are contrary to the 1945 Constitution and do not have binding legal force because they can detrimental to the constitutional rights of the Petitioners. If viewed according to Islamic law, the decision of the Constitutional Court has fulfilled a sense of justice for insurance participants and is in accordance with the basic principles of insurance in Islam.